Preparation And Evaluation Of Extended Release Trilayered Matrix Tablets Of Ramipril By Design of Experiment (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current work is aimed to design, prepare, and evaluate the trilayer matrix tablets incorporated with ramipril for extended drug release. Twenty-seven formulations (RF1-RF27) for active layer (middle layer) were prepared by direct compression method using 33 Response surface method of polymers of different HPMC K4M, HPMC K15M and xanthan gum (low, middle, and high concentrations) by using Design of experiment software. Based on physico-chemical properties and drug release one formulation was chosen and formulated into extended release trilayered matrix tablets were by varying proportions of polymers by direct compression method and they were evaluated. The best optimized formulation was characterized for FTIR studies. Out of 27 active layer formulations, RF23 was chosen as best based with maximum drug release of 98.11% and was formulated into extended release trilayered matrix tablets (ARF23-HRF23) by varying proportions of polymers. The range of swelling index for all batches (ARF23-HRF23) was 82.34 to 97.46%, similarly the range of drug content was 95.49 to 99.11% and drug released in 24 hours sustainably over an extended period was 84.98 to 98.26% with all highest values exhibited by GRF23. The release order kinetics data indicate the zero-order release with highest (R2) = 0.983 for GRF23 better when compared to marketed product which followed first order showed R2 value 0.962. Further the formulation (GRF23) showed best fit to Korsmeyer-Peppas plots i.e., 0.957 indicating non Fickian (anomalous) transport coupled diffusion and erosion. The FT-IR data assure the compatibility of drug and excipients. GRF23 was found to be stable for 180 days at accelerated conditions.